THE DIGITAL CLASSROOM: COMPARING THE EFFECTIVENESS OF ONLINE VS. TRADITIONAL LANGUAGE LEARNING (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article examines the comparative effectiveness of online and traditional (face-to-face) language learning in the context of rapidly expanding digital education technologies. Drawing on empirical studies in applied linguistics, educational psychology, and digital pedagogy, it evaluates strengths and limitations of both models across linguistic, cognitive, and motivational dimensions. Evidence suggests that online learning enhances accessibility and personalized instruction, while traditional classrooms remain superior for real-time communication and social learning. A blended approach is argued to be the most effective model.